Harmonizing the National Legal System Through the Formation of Ideal Legislation - Marikar, Moh. Fahriyanto (JURNAL LEGALITAS, 2023)
The purpose of this research is to find out and analyze an ideal formation of legislation in accordance with the times and the ideals of the Indonesian state as stated in the 1945 Constitution. This research uses the type of research used, namely normative-empirical (applied), which is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on any specific legal events that occur in society. Based on the results of the research, the researcher can conclude that a systemic approach to achieving legal harmonization can be carried out through several principles of approach, namely: analysis of the legal system as a whole, harmony and consistency between various legal regulations, consideration of legal impacts on society, and involvement of stakeholders in the harmonization process. Then, regarding harmonization in laws and regulations in Indonesia, in reality, there are still problems in the application of the hierarchy of laws and regulations. Such as the unclear position of the MPR Tap and Ministerial Regulations and also the position of existing Legislation in Article 7 and Article 8 of Law Number 12 of 2011 concerning the Formation of Legislation which is still confusing and not harmonious. Furthermore, to overcome the problems and juridical issues that exist in the Hierarchy of Legislation in Indonesia at this time the researcher modifies the Hierarchy of Indonesian Legislation as follows, the first order is filled by the 1945 Constitution of the Republic of Indonesia then the second order is filled by the Central Level Legislation, and the last is filled by regional level Legislation.